Design and analysis of a novel overload current estimation method for traditional miniature circuit breaker. Issue 10 (13th August 2020) - Lv, Sen; Zong, Ming; Yu, Siyang
Abstract : The power grid is developing towards intelligence. Therefore, as important electrical equipment of the power grid, miniature circuit breaker (MCB) should need to meet the requirements of the smart grid for terminal apparatuses. However, because the bending process of bimetal widely used in MCB overload protection is dispersive, which is difficult to realise electronisation, it is urgent to study the intelligent algorithm of MCB to protect the power grid well. For this purpose, a current calculation method based on temperature rise caused by load current of traditional non‐communicable MCB is proposed in this study. Compared with the present current calculation method, there is no iron core saturation problem even in the case of a huge load current. Also, in order to solve the problem of long time delay for stable temperature rise, a recursive algorithm that can rapidly calculate stable temperature rise is proposed. Furthermore, the current can be calculated rapidly. The influence of the initial temperature rise on the current calculation is also taken into account in the proposed algorithm. The simulation and experiment results show that the speed of stable temperature rise obtained by the recursive algorithm can meet the requirement of overload protection, and the error of calculating current is less than 5%.